Dinamika Pertukaran Peran Gender dalam Keluarga Pekerja Migran Perempuan: Studi Fenomenologis terhadap Suami di Ngrayun, Ponorogo - Cahyajati, Sri Yuda Mustika; Budirahayu, Tuti; Ariadi, Septi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study explores the dynamics of gender role exchange in Indonesian families where the wife becomes a migrant worker (PMI), focusing on the experiences of husbands who assume domestic responsibilities during their spouses' absence. Conducted in Ngrayun District, Ponorogo Regency—an area known for its high number of female PMIs—this research adopts a qualitative phenomenological approach involving seven male participants. The study investigates (1) societal perceptions of gender role reversal, (2) the challenges faced by husbands, and (3) their strategies for adaptation. Findings reveal that prolonged migration of wives often leads to negative social judgments, emotional strain, and domestic burdens on husbands. Despite these challenges, husbands demonstrate adaptive flexibility in gender roles through continued employment, emotional resilience, active parenting, and adherence to Javanese values of harmony. This study highlights the fluidity of gender constructs in traditional societies and calls for policy-level support to strengthen the well-being of transnational families.